The Role Of Political Television Advertisement Of The People's Assembly On The Electoral Participation For Postgraduate Students At Tishreen University (Latakia University Journal - Economic and Legal Sciences Series, 2020)
The study also aimed to: The degree of interest of graduate students at Tishreen University in political advertising. Statement of the impact of the TV political announcement on the electoral participation of graduate students in the elections of members of the People's Assembly. To reach some results that, if applied, can contribute to the development of the reality of political television advertising in the elections of the People's Assembly Methodology: Descriptive and analytical approach. Main findings of the study: There is no importance to members of the People's Assembly at Personal Advertising, Competitive Advertising, Educational Advertising. That lead to Negative impact about election process.  There is no importance to members of the People's Assembly at provisional TV Advertising That lead to Negative impact about election process. There is no impact on the political participation of the TV advertisement of personal advertisement, competitive advertisement and educational advertisement on the electoral participation of graduate students at Tishreen University. The main recommendation was increase the mental picture of members of the People's Assembly, Study the  TV experience advertisement of some country like ( USA, India, France), Increase the TV experience advertisement of  members of the People's Assembly.   هدفت الدراسة إلى الآتي: تحديد درجة اهتمام طلبة الدراسات العليا بجامعة تشرين بالإعلان السياسي التلفزيوني في سورية. وبيان تأثير الاعلان السياسي التلفزيون، على المشاركة الانتخابية لطلبة الدراسات العليا في انتخابات اعضاء مجلس الشعب في سورية. التوصل إلى بعض النتائج التي من الممكن في حال تطبيقها أن تساهم في تطوير واقع الاعلان التلفزيوني السياسي في انتخابات مجلس الشعب. تم إتباع المنهج الوصفي التحليلي. وقد كانت أهم النتائج التي توصلت لها الدراسة: عدم اهتمام أعضاء بالإعلان الشخصي والتنافسي والتثقيفي عبر التلفزيون مما يؤثر على مشاركة طلبة الدراسات العليا بالانتخابات واختيارهم بشكل سلبي. وعدم اهتمام أعضاء مجلس الشعب بالإعلان السياسي التلفزيوني بشكل احترافي مما يؤدي إلى عدم اهتمام طلبة الدراسات العليا بجامعة تشرين بهذا الاعلان نتيجة عدم وجودها أو جاذبيتها. وعدم وجود أثر للإعلان الشخصي لأعضاء مجلس الشعب على المشاركة الانتخابية لأعضاء الهيئة التدريسية في جامعة تشرين. وقد أوصت الدراسة بالآتي: العمل على تشكيل الصورة الذهنية المرغوبة من قبل الناخبين من خلال تغيير طريقة التعامل والتفاعل مع الناخبين وحل مشاكلهم، الاستفادة من  تجارب بعض الدول في مجال الاعلان السياسي التلفزيوني مثل( فرنسا، الهند، الولايات المتحدة الأمريكية)، زيادة اهتمام أعضاء مجلس الشعب بالإعلان السياسي التلفزيوني وذلك لما لهذه الطرق من أثر على تحسين المشاركة الانتخابية